OP18 Treatment of perianal fistulas in Crohn's Disease: Surgical closure after anti-TNF induction treatment versus anti-TNF without surgery (PISA II) - A patient preference RCT. (27th May 2021) - Meima - van Praag, E; van Rijn, K; Snijder, A; Wasmann, K; Stoker, J; D'Haens, G; Gecse, K; Gerhards, M; Jansen, J; Pronk, A; van Tyl, S; Zimmerman, D; et al.
Abstract: Background: Current guidelines on Crohn's perianal fistulas recommend anti-TNF treatment and suggest to consider surgical closure in amendable patients. However, long-term outcome of both treatments have not been directly compared. The aim of this study was to assess MRI healing in a patient preference RCT comparing both treatment modalities. Methods: This multicentre, international trial compared surgical closure following anti-TNF induction (4 months) to anti-TNF therapy without surgery. Patients were counselled for both treatment arms and randomised if there was no preference. Due to the combination of a preference and randomised cohort, the appropriate sample size to detect a clinically relevant increase of 25% closure (from 15% to 40%) was flexible and adjusted for a possible skewed distribution (86 patients in case of 1:1 treatment allocation). All Crohn's patients ≥ 18 years with a (re)active high perianal fistula and a single internal opening were eligible. Exclusion criteria were previous failure of anti-TNF, recto-vaginal fistula, proctitis, or stoma. Patients received seton placement prior to treatment. Primary outcome was MRI healing after 18 months (defined as a complete fibrotic fistula or MAGNIFI-CD score of 0–5). Secondary outcomes included clinical healing, re-interventions and fistula recurrence. Results: Between September 2013 and December 2019, 7 hospitals in the Netherlands and Italy included 93 patients (59% females, median age 34 years) of which 32 were randomised. Thirty-seven patients were treated in the surgical closure group and 56 in the anti-TNF group, with comparable baseline characteristics. After 18 months, MRI healing was significantly higher after surgical closure (41% vs 11%; P=0.002). Although a trend was seen in favour of surgical closure, clinical healing rates and surgical re-interventions were not significantly different between groups (65% vs 45%, P=0.07 and 19% vs 34%, P=0.1). After median 38 months follow-up, 12 patients in the anti-TNF group crossed over to surgical closure. Both long-term MRI healing and clinical closure in the per protocol analysis remained significantly higher for the surgical closure group (46% vs 11%, P=0.002 and 65% vs 29%, P=0.006). One patient (4%) with a MAGNIFI-CD score ≤5 developed a recurrent fistula after 46 months, whereas recurrences occurred in 37% of patients with MAGNIFI-CD score >5 (P=0.004). Conclusion: These results demonstrate that surgical closure following anti-TNF induction treatment induces MRI healing more frequently than anti-TNF alone. This is associated with increased long-term clinical closure and reduced recurrences. These data suggest that Crohn's perianal fistula patients amendable for surgical closure should be counselled for this therapeutic approach.